Ferric hydroxamate uptake system contributes to Edwardsiella ictaluri virulence. (November 2016) - Abdelhamed, Hossam; Lu, Jingjun; Lawrence, Mark L.; Karsi, Attila
Abstract: Edwardsiella ictaluri is a Gram-negative facultative intracellular pathogen causing enteric septicemia in fish, particularly in channel catfish. Ferric iron is an essential micronutrient for bacterial survival, and some bacterial pathogens use secreted hydroxamate-type siderophores to chelate iron in host tissues. Siderophore-iron complexes are taken up by these bacteria via the ferric hydroxamate uptake (Fhu) system. In E. ictaluri, the Fhu system consists of fhuC, fhuD, fhuB, and fhuA genes. However, the importance of the Fhu system in E. ictaluri virulence has not been investigated completely. Here, we present construction of E. ictaluri fhuD and fhuB mutants ( Ei Δ fhuD and Ei Δ fhuB ) by in-frame gene deletion and evaluation of the mutants' virulence and immunogenicity in channel catfish fingerlings and fry. Immersion challenges showed that Ei Δ fhuD was not significantly attenuated ( p  < 0.05) in catfish fingerlings, whereas Ei Δ fhuB was significantly attenuated ( p  < 0.01). Catfish fingerlings immunized with Ei Δ fhuD and Ei Δ fhuB showed 100% and 97.62% survival, respectively. Fry immersion challenges indicated Ei Δ fhuB was also significantly attenuated ( p  < 0.05) in two-week old fry compared to the wild-type (48.96% vs. 82.14% mortalities). The survival rate in the fry vaccinated with Ei Δ fhuB was significantly higher ( p  < 0.05) than that of non-vaccinated fry (96.77% vs. 21.42% survival). Our data indicates that the fhuB gene, but not the fhuD gene, contributes to E. ictaluri virulence. Highlights: The Fhu system consists of fhuC, fhuD, fhuB, and fhuA genes in E. ictaluri. The E. ictaluri fhuD and fhuB genes were mutated by in-frame deletion. The mutants' virulence and immunogenicity were evaluated in catfish. The E. ictaluri fhuB mutant was attenuated in catfish fingerlings and fry. The fhuB mutant protected catfish fingerlings and fry against E. ictaluri.